2020
DOI: 10.1186/s12891-020-03311-4
|View full text |Cite
|
Sign up to set email alerts
|

Compensation claims after knee cartilage surgery is rare. A registry-based study from Scandinavia from 2010 to 2015

Abstract: Background Focal cartilage defects (FCDs) in the knee joint has a high prevalence. A broad range of treatment options exists for symptomatic patients. Knowledge of patient compensation claims following surgical treatment of FCDs is missing. The purpose of this study is to evaluate compensation claims filed to the Scandinavian registries for patient compensation following treatment of FCDs in the knee joint from 2010 to 2015 and identify possible areas of improvement. Methods A cross-sectional study design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
5
6
0
Order By: Relevance
“…Pain was a common reason for claim ( Table 1 ). NPE registered 215 claims due to pain, although only 7 (3%) were accepted for compensation; pain alone does not serve as a cause for compensation, which is in line with previous reports from NPE (Clementsen et al 2018 , Randsborg et al 2018 , Aae et al 2020 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Pain was a common reason for claim ( Table 1 ). NPE registered 215 claims due to pain, although only 7 (3%) were accepted for compensation; pain alone does not serve as a cause for compensation, which is in line with previous reports from NPE (Clementsen et al 2018 , Randsborg et al 2018 , Aae et al 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…This is coherent with findings from Sweden, which stated that 49% of THA patients suffered an adverse advent that could have been prevented (Magnéli et al 2020 ). Delayed diagnosis or treatment and erroneous indications have previously been identified as avoidable causes for compensation (Clementsen et al 2018 , Randsborg et al 2018 , Aae et al 2020 ). During the study period, all hospitals in Norway implemented the use of the safe surgery protocol initiated by the World Health Organization (WHO 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for compensation was hospital-acquired infection. This is also the most common reason for accepted claims after other elective knee procedures, such as anterior cruciate ligament reconstruction and cartilage surgery (Randsborg et al 2018, Aae et al 2020. The proportion of accepted claims due to infection was particularly high for UKA compared with TKA (p = 0.06).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings serve as a reminder that nonoperative measures and correlation between radiological findings and clinical symptoms remain cornerstones in the indication for knee arthroplasty (Schmitt et al 2017). Unfortunately, avoidable treatment injuries such as wrong indication or inadequate follow-up remain major reasons for accepted claims in orthopedic surgery (Randsborg et al 2018, Aae et al 2020. These are modifiable factors and demonstrate how compensation claim reports can be useful for clinicians to learn from other people's mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in the UK and the US it is the judicial system that manages the injury compensation through tort liability. 10 Deilkås et al found a significantly higher rate of surgical adverse events in Norwegian hospitals (1.4%) compared to Swedish hospitals (.6%), which can be explained by a more centralized care in Sweden compared to Norway. 11 The relatively high early mortality and frailty (including cognitive impairment) in this patient group may decrease the likelihood of filing a complaint.…”
Section: Discussionmentioning
confidence: 96%